Age at diagnosis in patients with chronic congenital endocrine conditions: a regional cohort study from a reference center for rare diseases - Wafa Kallali (BMC, 2021)
Abstract Background For chronic congenital endocrine conditions, age at diagnosis is a key issue with implications for optimal management and psychological concerns. These conditions are associated with an increase in the risk of comorbid conditions, particularly as  it concerns growth, pubertal development and fertility potential. Clinical presentation and severity depend on the disorder and the patient’s age, but diagnosis is often late. Objective To evaluate age at diagnosis for the most frequent congenital endocrine diseases affecting growth and/or development. Patients and Methods This observational cohort study included all patients (n = 4379) with well-defined chronic congenital endocrine diseases—non-acquired isolated growth hormone deficiency (IGHD), isolated congenital hypogonadotropic hypogonadism (ICHH), ectopic neurohypophysis (NH), Turner syndrome (TS), McCune-Albright syndrome (MAS), complete androgen insensitivity syndrome (CAIS) and gonadal dysgenesis (GD)—included in the database of a single multisite reference center for rare endocrine growth and developmental disorders, over a period of 14 years. Patients with congenital hypothyroidism and adrenal hyperplasia were excluded as they are generally identified during neonatal screening. Results Median age at diagnosis depended on the disease: first year of life for GD, before the age of five years for ectopic NH and MAS, 8–10 years for IGHD, TS (11% diagnosed antenatally) and CAIS and 17.4 years for ICHH. One third of the patients were diagnosed before the age of five years. Diagnosis occurred in adulthood in 22% of cases for CAIS, 11.6% for TS, 8.8% for GD, 0.8% for ectopic NH, and 0.4% for IGHD. A male predominance (2/3) was observed for IGHD, ectopic NH, ICHH and GD. Conclusion The early recognition of growth/developmental failure during childhood is essential, to reduce time-to-diagnosis and improve outcomes.